Identificación de los servicios ecosistémicos que proveen las diferentes áreas protegidas en la Orinoquia colombiana (2016)
This study was conducted with the support of the Young Researchers and Innovators Program 2012- 2013 of Colciencias. The aim of the study was to develop a qualitative analysis of the ecosystem services provided by the land covers within the different categories of protected areas in the Orinoco basin. To achieve this goal, a matrix was constructed according to the capacities of the different land covers to provide ecosystem services and their respective conservation categories were analyzed. A survey of experts working on protected areas was also performed. As results was obtained for each protected area management category the number of hectares and the type of land cover and ecosystem were identified. Of the total number of surveys sent to experts, 19 were completed and additional information on 3 private reserves was obtained from interviews with the owners. As conclusions, the region has a variety of land covers with different capacities to provide regulation, provision and cultural ecosystem services. However, a complete analysis would require field work in each area in order to verify the matrix of provision capacities of ecosystem services. The information hereby presented may contribute to the effective management of the protected areas.